A Design-Based Research Approach for introducing Algorithmics and Programming to Bavarian Primary Schools: Theoretical Foundation and Didactic Implementation - Geldreich, Katharina; Simon, Alexandra; Hubwieser, Peter (MediaEducation: Journal for Theory and Practice of Media Education, 2019)
Computer Science (CS) is increasingly entering the early levels of childhood education, like primary school or even kindergarten. Although Germany has not yet developed mandatory guidelines for how to deal with these new topics, Bavaria seems to consider extending the field of computer science education to the primary sector in the long term. It is therefore becoming more and more necessary to gain insight into which teaching methods and content would be suitable for students at primary level. To investigate the characteristics of effective programming courses for primary schools, we developed a three-day introductory course following the design-based research approach. This article will set focus on both the theoretical foundation resulting from this specific research approach and the didactic implementation of the theoretical framework.